2018
DOI: 10.1007/s13205-018-1098-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of OglDREB2A gene from African rice (Oryza glaberrima), comparative analysis and its transcriptional regulation under salinity stress

Abstract: In this study, AP2 DNA-binding domain-containing transcription factor, was cloned from the African rice () and compared with 3000 rice genotypes. Further, the phylogenetic and various structural analysis was performed using in silico approaches. Further, to understand its allelic variation in rice, SNPs and indels were detected among the 3000 rice genotypes which indicated that while coding region is highly conserved, yet noncoding regions such as UTR and intron contained most of the variation. Phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Though DREB genes are mainly involved in the process regulating the drought stress, other functions have been noted for some DREB genes. Previous studies have demonstrated that DREB genes can be induced by various abiotic stresses, including drought [ 10 – 13 ], low temperatures [ 14 – 17 ], heat stress [ 18 – 20 ] and high salt [ 21 – 23 ]. Overexpressing OsDREB2A in soybean enhanced salt tolerance by accumulating osmolytes and improving the expression levels of some stress-responsive genes and TFs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though DREB genes are mainly involved in the process regulating the drought stress, other functions have been noted for some DREB genes. Previous studies have demonstrated that DREB genes can be induced by various abiotic stresses, including drought [ 10 – 13 ], low temperatures [ 14 – 17 ], heat stress [ 18 – 20 ] and high salt [ 21 – 23 ]. Overexpressing OsDREB2A in soybean enhanced salt tolerance by accumulating osmolytes and improving the expression levels of some stress-responsive genes and TFs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration responsive element-binding family genes have been identified in Arabidopsis thaliana (Hwang et al, 2012), perennial ryegrass (Xiong & Fei, 2006), Triticum L. (Mondini, Nachit & Pagnotta, 2015), Dendranthema (Yang et al, 2009), Zea mays (Qin et al, 2007) and Oryza sativa L. (Cui et al, 2011;Gumi et al, 2018;Matsukura et al, 2010). According to previous research in several plant species, most DREB genes respond to various stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recently, CBL4 and CBL9 were found to be related to drought stress in wheat [44]. Interestingly, LOC_Os02g06330 (AP2 domain containing protein) was found in the transcriptional regulation under salinity stress in African rice [63].…”
Section: Resultsmentioning
confidence: 99%